Pengembangan Sistem Informasi Manajemen Simpanan dan Pinjaman (Studi Kasus pada USIP PAMMAS) - I Putu Pradnyana Iswara; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
USIP PAMMAS is a non-governmental financial institution in Abiansemal District, Badung Regency, Bali Province, have task to managing the finances of their members within the scope of the local district community independently. Based on the results of an interview with Mr. Nyoman Piarsa as the chairman of the USIP institution, he said that there were difficulties in the implementation of the process of recording transaction activities within the organization. Currently, the process is still done manually and as the number of members increases, the tasks carried out by the staffs become increasingly difficult. Therefore, based on the problems described previously, the offered solution is to develop an information system for deposit and loan management to handle them. System development is done by using the Waterfall method and implemented with a web-based application, using the Laravel framework. The steps taken include requirement analysis, design, implementation, and testing. For system validation testing results based on functional requirements, from 8 test cases all get valid results. For the results of the compatibility test, the system runs with the same functionality on all tested browser using SortSite application. For the User Acceptance Testing result, the test is given to two actors, first one is admin actors represented by the USIP chairman (94% UAT percentage value) and secondly USIP management actors represented by USIP staff (95% UAT percentage value).